Differential KrasV12 protein levels control a switch regulating lung cancer cell morphology and motility. (20th September 2016) - Schäfer, C; Mohan, A; Burford, W; Driscoll, M K; Ludlow, A T; Wright, W E; Shay, J W; Danuser, G
Abstract: Oncogenic Kras mutations are important drivers of lung cancer development and metastasis. They are known to activate numerous cellular signaling pathways implicated in enhanced proliferation, survival, tumorigenicity and motility during malignant progression. Most previous studies of Kras in cancer have focused on the comparison of cell states in the absence or presence of oncogenic Kras mutations. Here we show that differential expression of the constitutively active mutation Kras V12 has profound effects on cell morphology and motility that drive metastatic processes. The study relies on lung cancer cell transformation models, patient-derived lung cancer cell lines, and human lung tumor sections combined with molecular biology techniques, live-cell imaging and staining methods. Our analysis shows two cell functional states driven by Kras V12 protein levels: a non-motile state associated with high Kras V12 levels and tumorigenicity, and a motile state associated with low Kras V12 levels and cell dissemination. Conversion between the states is conferred by differential activation of a mechano-sensitive double-negative feedback between Kras V12 /ERK/Myosin II and matrix-adhesion signaling. Kras V12 expression levels change upon cues such as hypoxia and integrin-mediated cell-matrix adhesion, rendering Kras V12 levels an integrator of micro-environmental signals that translate into cellular function. By live cell imaging of tumor models we observe shedding of mixed high and low Kras V12 expressers forming multi-functional collectives with potentially optimal metastatic properties composed of a highly mobile and a highly tumorigenic unit. Together these data highlight previously unappreciated roles for the quantitative effects of expression level variation of oncogenic signaling molecules in conferring fundamental alterations in cell function regulation required for cancer progression.